Data Driven Quality Improvement of Health Professions Education: Design and Development of CLUE – An Interactive Curriculum Data Visualization Tool - Canning, Claire Ann (IOS Press, 2017)
Curriculum Mapping and dynamic visualization is quickly becoming an integral aspect of quality improvement in support of innovations which drive curriculum quality assurance processes in medical education. CLUE (Curriculum Explorer) a highly interactive, engaging and independent platform was developed to support curriculum transparency, enhance student engagement, and enable granular search and display. Reflecting a design based approach to meet the needs of the school's varied stakeholders, CLUE employs an iterative and reflective approach to drive the evolution of its platform, as it seeks to accommodate the ever-changing needs of our stakeholders in the fast pace world of medicine and medical education today. CLUE exists independent of institutional systems and in this way, is uniquely positioned to deliver a data driven quality improvement resource, easily adaptable for use by any member of our health care professions.